A Twin Study of Cigarette and Snus Initiation and Quantity of Use in Norwegian Adult Twins. (22nd April 2019) - Kendler, Kenneth S.; Aggen, Steven H.; Gillespie, Nathan; Czajkowski, Nikolai; Ystrom, Eivind; Reichborn-Kjennerud, Ted
Abstract: While snus has been the focus of increasing public health interest, twin studies have examined neither sources of individual variation for its use nor the sources of resemblance between snus and cigarette use. Twins from the Norwegian Institute of Public Health Panel were assessed by self-report questionnaire for the initiation of regular use and maximal quantity used for snus and cigarettes. Twin modeling was performed using OpenMx on data from 2767 twins including 856 complete pairs. Fitting univariate twin models produced similar results for cigarette initiation and quantity with estimates of additive genetic, shared environmental and unique environmental effects of approximately 77%, 0% and 23%, respectively. Estimates of snus initiation and quantity were, respectively, approximately 53%, 26% and 21%. Joint analyses suggested that the genetic, shared environmental and unique environmental correlations between cigarette and snus initiation and quantity were +.82, 0 and +.42, respectively. However, these results could not be statistically distinguished from a model which postulated that resemblance between cigarette initiation and quantity resulted from genetic and unique environmental correlations of +.47 and +.43. Compared with cigarette initiation and quantity of use in Norwegian twins, the role of genes was less prominent and shared environment more prominent for initiation and quantity of use of snus. Joint analyses of both tobacco phenotypes suggested, but did not confirm definitively, that genetic risk factors for cigarette and snus use were similar but not identical, while shared environmental factors existed that were specific to snus use.